SuperBreak: Using Interactivity to Enhance Ergonomic Typing Breaks - Morris, Dan; Brush, A.J.; Meyers, Brian (CHI '08 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2008)
Repetitive strain injuries and ergonomics concerns have become increasingly significant health issues as a growing number of individuals frequently use computers for long periods of time. Currently, limited software mechanisms exist for managing ergonomics; the most well-known are “break-reminder” packages that schedule and recommend typing breaks. Yet despite the proven benefits of taking breaks, such packages are rarely adopted due to the overhead of introducing periodic interruptions into a user’s workflow. In this paper, we describe SuperBreak, a break reminder package that provides hands-free interactions during breaks, with the goal of encouraging users to take more breaks and enhancing the benefits of those breaks. In a field study of 26 knowledge workers, 85% preferred SuperBreak over a traditional break-reminder system, and on average participants took a higher percentage of the interactive breaks suggested to them. Our results highlight the value of interactivity for improving the adoption and retention of ergonomic break practices.